The Role of Higher Education Institutions in the Entrepreneurship of Hungarian Students1 - S. Gubik, Andrea (Theory, Methodology, Practice – Review of Business and Management, 2014)
Entrepreneurial activity is a decisive factor in the dynamics of job creation and economic growth. That is why it is crucial to identify the most important factors influencing the attitudes and the entrepreneurial intentions towards entrepreneurship and to determine the possible fields of intervention targeting the creation of as many new and viable enterprises as possible. Although education may play an important role in entrepreneurship, its direct impact has not yet been revealed. Education may be crucial in awaking of entrepreneurial thinking, in obtaining the basic knowledge about starting and running one’s own business and in directly promoting enterprises. The Hungarian database of the GUESSS research project, with almost 6,000 respondents, helps us to evaluate the role of education on entrepreneurship. We compare the course, service and resource supply of Hungarian higher education institutions and the exploitation of them by Hungarian students, than we highlight the positive relationship between the efforts of colleges and universities and the entrepreneurial intentions and activities of students.